Prevalence of Depression and Burnout among Family Medicine Residents in Riyadh City, Saudi Arabia - Alaa AlNahedh; Asma BinRusayyis; Mohamad Al-Tannir; Isamme AlFayyad (Health Psychology Research)
# Background